(untitled) (One Health Journal of Nepal, 2023)
Chondrodysplasia Punctata (CDP) is a genetic disorder with skeletal and developmental abnormalities. This case report describes the clinical features, diagnostic evaluation, management, and genetic counselling of patients with CDP. This report aimed to increase awareness about this condition and importance of early diagnosis, multidisciplinary management care, and genetic counselling for better patient outcomes.